(untitled) (Aqwal: Journal of Qur’an and Hadis Studies, 2026)
Background and Objectives: This study examines maternal anxiety and psychological resilience in the interpretation of Qur’anic verses related to pregnancy through a comparative analysis of the exegetical works of Muhammad Mutawalli al-Sha‘rawi and Bint al-Shati’. The study is motivated by the tendency of Qur’anic exegesis to focus predominantly on legal and theological dimensions, while the emotional and psychological experiences of women during pregnancy receive relatively limited attention. This research aims to explore how maternal anxiety and psychological resilience are conceptualized in the interpretations of both exegetes and to identify the similarities and differences between their perspectives. Method: Employing a library research method and a comparative (muqaran) tafsir approach, the study analyzes key Qur’anic passages concerning pregnancy and childbirth, particularly Q.S. Maryam [19]: 22–23, Q.S. Luqman [31]: 14, and Q.S. Al-Ahqaf [46]: 15. Main Results: The findings reveal that al-Sha‘rawi interprets maternal suffering within a spiritual and moral framework that emphasizes patience, divine wisdom, and devotion to God. In contrast, Bint al-Shati’ offers a more humanistic perspective by highlighting women’s emotional experiences, including fear, loneliness, anxiety, and psychological endurance throughout pregnancy and childbirth. Contributions: This research contributes to enriching the study of interpretation in the aspect of thematic interpretation of the Qur’an and its integration with the psychology of pregnant women contained in the Qur’an. Conclusions: The study concludes that both exegetes provide complementary perspectives: al-Sha‘rawi’s spiritual-transcendental approach and Bint al-Shati’s humanistic-psychological approach. Together, these interpretations enrich contemporary understandings of motherhood and women’s psychological experiences as represented in the Qur’an. Keywords: maternal anxiety, psychological resilience, pregnancy, comparative tafsir, al-Sha‘rawi, Bint al-Shati’.